Electronics reliability and measurement technology : nondestructive evaluation - Heyman, Joseph S. (Noyes Data Corp., 1988)
This book examines electronics reliability and measurement technology. It identifies advances in measurement science and technology for nondestructive evaluation, and it details common measurement trouble spots.